The cinema of Rithy Panh : everything has a soul - Barnes, Leslie, 1976- (Global film directors, 2021)
Born in 1964, Cambodian filmmaker Rithy Panh grew up in the midst of the Khmer Rouge's genocidal reign of terror, which claimed the lives of many of his relatives. After escaping to France, where he attended film school, he returned to his homeland in the late 1980s and began work on the documentaries and fiction films that have made him Cambodia's most celebrated living director. The fourteen essays in The Cinema of Rithy Panh explore the filmmaker's unique aesthetic sensibility, examining the dynamic and sensuous images through which he suggests that "everything has a soul." They consider how Panh represents Cambodia's traumatic past, combining forms of individual and collective remembrance, and the implications of this past for Cambodia's transition into a global present. Covering documentary and feature films, including his literary adaptations of Marguerite Duras and Kenzaburō Ōe, they examine how Panh's attention to local context leads to a deep understanding of such major themes in global cinema as justice, imperialism, diaspora, gender, and labor. Offering fresh takes on masterworks like The Missing Picture and S-21 while also shining a light on the director's lesser-known films, The Cinema of Rithy Panh will give readers a new appreciation for the boundless creativity and ethical sensitivity of one of Southeast Asia's cinematic visionaries.